A practical measurement of thoracic sarcopenia: correlation with clinical parameters and outcomes in advanced lung cancer. Issue 2 (13th April 2016) - Wysham, Nicholas G.; Nipp, Ryan D.; LeBlanc, Thomas W.; Wolf, Steven P.; Ekstrom, Magnus P.; Currow, David C.
Sarcopenia, the loss of skeletal muscle mass, is common in chronic disease, and has been hypothesised to contribute to fatigue and breathlessness [1, 2]. The research gold standard for assessing sarcopenia relies on whole-body, cross-sectional imaging, an impractical approach in routine care [3]. A more practical alternative measures lumbar skeletal muscle density at L3 using computed tomography (CT) normalised for height, termed the skeletal muscle index (SMI) [4]. While evidence suggests that reduced lumbar SMI correlates with adverse clinical outcomes, such as mortality in lung or colorectal cancers [5], little research has explored how this measure of sarcopenia relates to breathlessness or exercise tolerance. Thoracic sarcopenia can feasibly be measured from routine CT scans but does not correlate to patient-centred outcomes http://ow.ly/102UkQ